2013
DOI: 10.1590/s0100-83582013000300015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of irrigated rice sowing season and imazapyr + imazapic time of application on rice grain yield and red rice management

Abstract: -Irrigated rice sowing season and red rice competition are among the main factors affecting grain yield. The objective of this work was to evaluate the sowing date of irrigated rice and moments of application of the herbicide imazapyr + imazapic to control red rice management and irrigated rice grain yield. Eight experiments were performed at the following dates (09/30, 10/19, 11/08 and 12/01) for the 2010/2011 harvest season and (09/27, 10/17, 11/08 and 12/05) for the 2011/2012 harvest season. The treatments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“…), which might have triggered the evolution of resistance to imazapyr in weedy rice populations (e.g., population C). Sartori et al [ 42 ] opined that pre-emergence application of imazapic was effective in controlling weedy rice. A similar outcome was reported by Washburn and Barnes [ 43 ], who observed that pre-emergence application of imazapic was more effective in controlling grass weeds than post-emergence application.…”
Section: Discussionmentioning
confidence: 99%
“…), which might have triggered the evolution of resistance to imazapyr in weedy rice populations (e.g., population C). Sartori et al [ 42 ] opined that pre-emergence application of imazapic was effective in controlling weedy rice. A similar outcome was reported by Washburn and Barnes [ 43 ], who observed that pre-emergence application of imazapic was more effective in controlling grass weeds than post-emergence application.…”
Section: Discussionmentioning
confidence: 99%
“…The IMI-herbicides OnDuty™ WG premix comprise of imazapic (52.5%) and imazapyr (17.5%) as active ingredients. Sartori et al [29] opined that the application of imazapic as pre-emergence was effective in controlling weedy rice. Similar outcome was reported by Washburn and Barnes [30] where pre-emergence application of imazapic was effective to control grass weeds compared to post-emergence application.…”
Section: Discussionmentioning
confidence: 99%
“…Galon et al (2012) observaram que imazapyr + imazapic (73,5 + 24,5 g ha -1 ) foi eficiente para o controle de arroz-daninho, em aplicação de pós-emergência em plantas oriundas de sementes. Sartori et al (2013) relataram controle eficiente arroz-daninho com a aplicação de imazapyr + imazapic tanto em aplicação de pré quanto de pós-emergência. Resultados semelhantes também foram descritos por Marchesan et al (2011).…”
Section: Genótiposunclassified